Reliability & safety for embedded systems - Schwamm, F (IEE Seminar on Safety Critical Applications from Aerospace to Automotive, 2006)
Presentation slides on the subject of reliability and safety considerations for embedded systems. Particular reference is made the application in embedded control systems of aerospace and automotive vehicles.